Chemical Composition, Antioxidant and Antimicrobial Activity of the Essential Oil of Phellodendron amurense (Rupr.) from China - Han, Y.; Xu, L.; Wang, Q.; Huang, Y.; Meng, W. (Asian Journal of Chemistry, 2015)
The essential oil of Phellodendron amurense has been isolated from fruits collected in their native habitat China. Hydrodistillation of P. amurense afforded a pale yellow oil in 1.4 % (w/w) yield. The chemical composition of this essential oil was analyzed by GC-MS. Twenty-one compounds were identified, accounting for 97 % of the total oil. There were five most abundant constituents (greater than 5 %) were myrcene (51.7 %), 2-methyl-6-methyleneocta-3,7-dien-2-ol (7.4 %), 1,2-benzenedicarboxylic acid-bis(2-methylpropyl)-ester (7.2 %), 2-methyl-6-methyleneocta-1,7-dien-3-ol (7.1 %) and a-phellandrene (5.2 %).The essential oil of P. amurense showed antioxidant activity (IC50, 2.32 μg/mL) and broad spectrum fumigant and contact antimicrobial activity against all microbial strains tested (MIC or IC50, 0.12-1.36 μg/mL). These findings suggest that the essential oil may be used as an antioxidant or antimicrobial agent.